2010
DOI: 10.1007/s00784-010-0382-1
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic suitability of a xerostomia questionnaire and the association between xerostomia, hyposalivation and medication use in a group of nursing home residents

Abstract: The study objective was to explore the diagnostic suitability of the Xerostomia Inventory and the association between xerostomia, hyposalivation and medication use in a group of nursing home residents. A cross-sectional study was carried out in 50 physically impaired nursing home residents (20 men) with a mean age of 78.1 years (range, 53–98) in The Netherlands. The Xerostomia Inventory-Dutch version was completed for all residents and the data were subjected to exploratory factor analysis to determine the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 48 publications
5
69
1
7
Order By: Relevance
“…This was done in the Dutch study 11 because the participants found it difficult to distinguish the five response options, and we repeated it in the secondary analyses of the data from the other four studies. Was this likely to have affected the discriminative properties of the measure?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done in the Dutch study 11 because the participants found it difficult to distinguish the five response options, and we repeated it in the secondary analyses of the data from the other four studies. Was this likely to have affected the discriminative properties of the measure?…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to investigate whether shortening the measure by omitting those items unduly compromises its psychometric or statistical characteristics. A recent Dutch study 11 of 55 nursing home residents used such a shortened version, along with a reduction in Guttman-type response options from the usual five to three, occasioned by difficulties experienced by the participants in discriminating among the five response options. The findings of that study indicated that the shortened measure (dubbed the “Summated Xerostomia Inventory-Dutch Version”) appeared to be valid, but that there is a need to determine the shortened measure’s validity and properties in larger and more diverse samples and settings before any recommendations on its future use can be made.…”
Section: Introductionmentioning
confidence: 99%
“…However, xerostomia is subjective with different symptoms, and thus, its assessment can only be performed by questionnaires using discriminative questions (van der Putten et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Xerostomia is a common symptom in patients seeking help from specialists in oral medicine (Orellana et al, ; van der Putten, Brand, Schols, & de Baat, ). Among other reasons, it is often a side effect of head and neck radiation and can impair multiple oral functions such as speech and swallowing, leading to poorer quality of life (QoL) (Eisbruch et al, ).…”
Section: Introductionmentioning
confidence: 99%